Cytokine storm in severe COVID‐19 pneumonia - Gürsoy, Bengül (J Med Virol, 2021)
In this study, laboratorial parameters of hospitalized novel coronavirus (COVID‐19) patients, who were complicated with severe pneumonia, were compared with the findings of cytokine storm developing in macrophage activation syndrome (MAS)/secondary hemophagocytic lymphohistiocytosis (sHLH). Severe pneumonia occurred as a result of cytokine storm in some patients who needed intensive care unit (ICU), and it is aimed to determine the precursive parameters in this situation. Also in this study, the aim is to identify laboratory criteria that predict worsening disease and ICU intensification, as well as the development of cytokine storm. This article comprises a retrospective cohort study of patients admitted to a single institution with COVID‐19 pneumonia. This study includes 150 confirmed COVID‐19 patients with severe pneumonia. When they were considered as severe pneumonia patients, the clinic and laboratory parameters of this group are compared with H‐score criteria. Patients are divided into two subgroups; patients with worsened symptoms who were transferred into tertiary ICU, and patients with stable symptoms followed in the clinic. For the patients with confirmed COVID‐19 infection, after they become complicated with severe pneumonia, lymphocytopenia (55.3%), anemia (12.0%), thrombocytopenia (19.3%), hyperferritinemia (72.5%), hyperfibrinogenemia (63.7%) and elevated lactate dehydrogenase (LDH) (90.8%), aspartate aminotransaminase (AST) (31.3%), alanine aminotransaminase (ALT) (20.7%) are detected. There were no significant changes in other parameters. Blood parameters between the pre‐ICU period and the ICU period (in which their situation had been worsened and acute respiratory distress syndrome [ARDS] was developed) were also compared. In the latter group lymphocyte levels were found significantly reduced (p = 0.01), and LDH, highly sensitive troponin (hs‐troponin), procalcitonin, and triglyceride levels were significantly increased (p < 0.05). In addition, there was no change in hemoglobin, leukocyte, platelet, ferritin, and liver function test levels, including patients who developed ARDS, similar to the cytokine storm developed in MAS/sHLH. COVID‐19 pneumonia has similar findings as hyperinflammatory syndromes but does not seem to have typical features as in cytokine storm developed in MAS/sHLH. In the severe patient group who has started to develop ARDS signs, a decrease in lymphocyte level in addition to the elevated LDH, hs‐troponin, procalcitonin, and triglyceride levels can be a predictor in progression to ICU admission and could help in the planning of anti‐cytokine therapy.